The Effect of Extraction Parameters on Antioxidant Activity of Cosmos Caudatus - Badariah, Mohd Nasir (2013)
The present of natural antioxidant in plant is well known and Cosmos caudatus is one of the plants that have high content of antioxidant. The objective of this study was to investigate the effect of operating conditions on extraction of total antioxidant compound (TAC) from C. caudatus. TAC was extracted using 70 % (v/v) acetone as the solvent for 4, 8 hour and 12 hours. C. caudatus was then extracted at different to solid to solvent ratio of 1:20, 1:25 and 1:30 (w/v). Finally, C. caudatus was extracted at different extraction temperature (60, 80 and 100 oC) for 30 min. The results show that the best extraction time to extract the TAC was after 8 hour extraction using solvent to sample ratio of 1:30 (w/v) and 66 oC of extraction temperature. The TAC obtained was 28.8 mg AAE/g with the corresponding of 10.1% of its antioxidant activity. However, when considered the extraction temperature, the highest value of TAC (19.5 mg AAE/g) was observed in extraction at 80o C after 30 minute and for temperature 60 and 100 oC the TAC were 16.4 and 17.1 mg AAE/g. In HPLC analysis using the ratio sample to solvent at 8 hour, the highest TAC was at 1:30 (2.368 mg AAE/g) and also for the extraction temperature 80 oC has highest TAC (1.84611 mg AAE/g). This trend was similar with the result obtained from DPPH assay where 1:30 (w/v) and at 80 oC extraction has highest TAC.